DESIGNING 64-BIT BLOCK CIPHER CRYPTOGRAPHY BASED ON THE PATTERN OF ONE OF KARO'S TRADITIONAL CLOTHS - Dandy Duggari Manik; Somya, Ramos (Informatika, Universitas Jenderal Soedirman, 2024)
The ease of access to information technology in the modern era can be felt in various aspects of human life needs, one of which is exchanging information or exchanging data is an activity that has been carried out very often every day. With this convenience, the security and confidentiality of the data is also very important to consider because the information or data exchanged can contain important or confidential matters. In the exchange of data or information, of course, a security system is needed that ensures the data remains safe. One of the techniques to secure this data is to use cryptographic techniques. There have been many cryptographic techniques used or implemented to secure information, but many cryptographic techniques have been solved so that the ability to secure data is doubtful. One way to overcome this is to create a new cryptography or make changes to existing cryptography. Through this research, a cryptography will be created that uses the pattern of Karo traditional cloth and uses a 64-bit Block Cipher to produce a better encryption process.